2009
DOI: 10.1111/j.1365-2265.2009.03545.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular dysgenesis syndrome: foetal origin of adult reproductive problems

Abstract: SummaryThe evidence for the existence of testicular dysgenesis syndrome (TDS) is presented in this review. Several epidemiological studies have shown that conditions like cryptorchidism, impaired spermatogenesis, hypospadias and testicular cancer can be associated as risk factors for each other. Thus, the risk of testis cancer is significantly increased in men with cryptorchidism and/or infertility. Several recent studies point towards early dysgenesis of the foetal testis as the biological link between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(122 citation statements)
references
References 70 publications
4
109
0
5
Order By: Relevance
“…This observation lead to the theory of the testicular dysgenesis syndrome which includes all the four above mentioned pathologies. 32 Congenital and acquired cryptorchidism are both very common but may have different etiology and consequences for fertility may also be different.…”
Section: Varicocelementioning
confidence: 99%
“…This observation lead to the theory of the testicular dysgenesis syndrome which includes all the four above mentioned pathologies. 32 Congenital and acquired cryptorchidism are both very common but may have different etiology and consequences for fertility may also be different.…”
Section: Varicocelementioning
confidence: 99%
“…To what degree the environment, genetics, or epigenetics during fetal growth are responsible for TDS remains unresolved, but consensus is building concerning an expanded role for environmental influences and exposures (Virtanen et al, 2005;Wohlfahrt-Veje et al, 2009;Nordkap et al, 2012;Skakkebaek et al, 2016). Therefore, investigating semen parameters in relation to familial early-life mortality represents an area of novel contribution to the TDS hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, increased understanding of Sertoli cell proliferation and development is important to those interested in animal agriculture. As abnormalities in Sertoli cell development and proliferation contribute to testicular dysgenesis syndrome in humans (Wohlfahrt-Veje et al 2009), increased understanding is also important to the biomedical community. Previous studies in our laboratory have demonstrated that the administration of letrozole, an inhibitor of estrogen synthesis, beginning in the neonatal period promotes proliferation of Sertoli cells in boars.…”
Section: Introductionmentioning
confidence: 99%